2003
DOI: 10.1021/ar020177t
|View full text |Cite
|
Sign up to set email alerts
|

Petroleomics:  The Next Grand Challenge for Chemical Analysis

Abstract: Ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry has recently revealed that petroleum crude oil contains heteroatom-containing (N,O,S) organic components having more than 20,000 distinct elemental compositions (C(c)H(h)N(n)O(o)S(s)). It is therefore now possible to contemplate the ultimate characterization of all of the chemical constituents of petroleum, along with their interactions and reactivity, a concept we denote as "petroleomics". Such knowledge has already proved capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
638
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 727 publications
(652 citation statements)
references
References 51 publications
7
638
0
Order By: Relevance
“…heavy fuel oil) in petroleomics [1][2][3][4][5][6][7] . Fourier transform ion cyclotron resonance mass spectrometry (FT-ICRMS) is most commonly used, due to its high resolving power [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…heavy fuel oil) in petroleomics [1][2][3][4][5][6][7] . Fourier transform ion cyclotron resonance mass spectrometry (FT-ICRMS) is most commonly used, due to its high resolving power [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new concept and research method of Petroleomics had been formed in the field of petroleum chemistry, which mainly studies the relationship between the molecular constitutes and their physical, chemical properties, process performance etc. (Marshall et al, 2004;Rodgers et al, 2005), based on the elaborate characterization of the petroleum molecules at molecular level. Previous studies showed that through chemical methylation treatment, thioether, and thiophenic etc.…”
mentioning
confidence: 99%
“…C omplex organic mixture characterization by mass analysis requires the ultrahigh mass resolving power of Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) [1] to distinguish thousands of ionic species simultaneously [2,3]. Electrospray ionization (ESI) of polar analytes typically involves proton transfer reactions that selectively ionize acids (to produce negative [MϪH] Ϫ ions) or bases (to produce positive [MϩH] ϩ ions) [3][4][5][6].…”
mentioning
confidence: 99%